Pengaruh Work Life Balance dan Beban Kerja terhadap Turnover Intention melalui Stres Kerja Karyawan : Studi Kasus: PT Semarang Garment - Santika Delviani Ramadhani; Rauly Sijabat; Shofif Sobaruddin Akbar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of work-life balance and workload on turnover intention, with work stress as a mediating variable in employees of PT Semarang Garment. The phenomenon of high turnover in the garment industry is the background of this study, which is triggered by large production targets, high work pressure, and imbalance between work and personal life. These conditions have the potential to reduce employee welfare and increase the desire to leave the company. This study uses a quantitative method with Structural Equation Modeling (SEM) analysis techniques using AMOS version 24. The research sample of 360 respondents was selected through a simple random sampling technique, and data was collected using a structured online questionnaire. The results of the analysis show that: (1) Work-life balance does not have a significant effect on turnover intention, but has a significant negative effect on work stress, which means the better the work-life balance, the lower the level of work stress; (2) Workload has a significant positive effect on work stress, but does not have a significant effect on turnover intention; (3) Work stress has a significant positive effect on turnover intention, which indicates that the higher the work stress, the greater the employee's desire to leave. Furthermore, it was found that job stress mediates the relationship between work-life balance and turnover intention, so improving work-life balance can indirectly reduce turnover intention through reduced job stress. Theoretically, this study adds to the human resource management literature on factors influencing turnover intention. Practically, the results recommend that company management create a healthy work environment, manage workloads proportionally, and design policies that support work-life balance to reduce turnover intention.